Miles and maternity: a survey of long-duration exercise during pregnancy - Bains, G.; Hayman, M. J.; Kolker, S.; Davenport, M. H. (Sports Medicine, 2025)
Introduction: Global pregnancy physical activity guidelines recommend most individuals engage in at least 150 min/week of moderate-to-vigorous physical activity. However, exercise beyond these limits has received little investigation and assessment of safety. There is no consensus on safe durations of exercise bouts within the literature, with recommendations ranging from 10 to 60 min. Objective: The aim was to examine the impact of long-duration endurance exercise (= 60 min/session) on maternal-fetal health outcomes. Methods: A total of 331 participants who engaged in long-duration endurance exercise during pregnancy participated in an online survey. Results: Participants were aged 33.2 ± 6.1 years and had 2.1 ± 1.2 pregnancies. Subgroup analyses were performed comparing: (1) those who exercised within guidelines, = 300 min/week during the third trimester (T3), and (2) those who exercised above guidelines, > 300 min/week during T3. Participants who exceeded guidelines experienced reduced odds of delivery complications (odds ratio [OR] 0.12, 95% confidence interval [CI] 0.015-0.988, p < 0.05) but increased the odds of diastasis recti abdominis postpartum (OR 4.13, 95% CI 1.059-16.135, p < 0.05). Conclusion: Exercising > 300 min/week in T3 reduces odds of delivery complications, but increases odds of diastasis recti abdominis postpartum. Endurance exercise > 300 min/week in T3 is generally well tolerated in a highly active population.